Edukacja językowa w Polsce: stan, wyzwania i perspektywy rozwoju. Część II: Nauczanie dwujęzyczne i CLIL - Banasiak, Ilona; Olpińska-Szkiełko, Magdalena; Patera, Mateusz (Neofilolog, 2025)
The report examines bilingual education in Poland, focusing on the Content and Language Integrated Learning (CLIL) approach. It outlines the history of bilingual education, variations in programs, and the current enrollment of students and institutions in bilingual education. In Poland, the predominant bilingual education is in English, but the overall availability of bilingual education is limited and varies by region. The Polish education system is confronted with several significant challenges, such as the need to improve language teaching overall, particularly for languages taught as additional foreign languages, better support for the learning of languages other than English, and more significant endorsement for teaching national minority, ethnic, and regional languages. The increasing public interest in multilingualism and the engagement of researchers, educators, and policymakers in addressing these societal needs inspire hope that the Polish education system will soon take better advantage of the opportunities provided by bilingual programs.